2022
DOI: 10.1021/acsomega.2c04787
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Mechanism of Some Vinylalkylimidazolium-Based Polymeric Ionic Liquids against Acid Corrosion of API 5L X60 Steel: Electrochemical and Surface Studies

Abstract: A corrosion inhibition mechanism of API 5L X60 steel exposed to 1.0 M H 2 SO 4 was proposed from the evaluation of three vinylalkylimidazolium poly(ionic liquids) (PILs), employing electrochemical and surface analysis techniques. The synthesized PILs were classified as mixed-type inhibitors whose surface adsorption was promoted mainly by bromide and imidazolate ions, which along with vinylimidazolium cations exerted a resistive effect driven by a charge transfer process by means of a protective PIL film with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…It can be observed that the R ct values are a function of C INH , where the highest results occurred at 175 ppm. The polarization resistance exhibited by the system by the EIS ( Rp EIS ) technique involves all the EEC resistive elements [ 28 ]. The Rp EIS values in the presence of the PILs were higher than those shown by the blank at the different temperatures, indicating higher resistance to the electron transfer in the electrochemical reactions involved in the corrosion process and confirming the inhibiting behavior of the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that the R ct values are a function of C INH , where the highest results occurred at 175 ppm. The polarization resistance exhibited by the system by the EIS ( Rp EIS ) technique involves all the EEC resistive elements [ 28 ]. The Rp EIS values in the presence of the PILs were higher than those shown by the blank at the different temperatures, indicating higher resistance to the electron transfer in the electrochemical reactions involved in the corrosion process and confirming the inhibiting behavior of the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Table 9 shows the chemical structures of the compounds evaluated as CIs: Poly(1-butyl-3-vinylimidazolium)imidazolate, Poly[VIMC4][Im], Poly(acrylamide-N-vinylpyrrolidone-1-ethyl-3-vinylimidazolium bromide), Poly[VIMC2][Br], and Poly(acrylamide-N-vinylpyrrolidone-1-butyl-3-vinylimidazolium bromide), Poly[VIMC4][Br]. The synthesis and characterization of the PILs was already reported in a previous work [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gómez-Sánchez et al 249 evaluated three vinylalkaylimidazolium PILs (poly[VIMC 2 ][Br], poly[VIMC 4 ][Br], and poly[VIMC 4 ][IM]), employing electrochemical and surface analysis techniques in 1 M H 2 SO 4 and reported that the steel surface displayed less surface damage due to the formation of metal–PIL complex compounds. As shown in Fig.…”
Section: Applicationmentioning
confidence: 99%
“…In this context, polymeric ILs or poly­(ionic liquids) (PILs) have stood out because of their additional advantage before conventional polymeric compounds by possessing ions with a polymeric structure. Gómez-Sánchez et al , proposed the study of three PILs as CIs for API X60 steel in 1 M H 2 SO 4 : PILs with cations derived from acrylamide, vinyl­pyrrolidone, and 1-alkyl-3-vinyl­imidazolium, and bromide and imidazolate anions (Table ). According to the electrochemical evaluation, the best IE was displayed by PILs with different N-heteroatom and/or N-heterocycle blocks, thus confirming the synergistic effect of the bromide ion as well as the inhibiting activity of the substituted imidazolium ring.…”
Section: Corrosion Inhibitorsmentioning
confidence: 99%